Training on creating augmented reality-based flash card for SMAIT Al-Fityan teachers - Hanum Mukti Rahayu; Dedeh Kurniasih; Ari Sunandar; Nengsih Nengsih (Universitas Muhammadiyah Magelang, 2024)
Learning media plays a crucial role in supporting the educational process, especially in the 21st century, which demands technological innovation. Based on observations and interviews with teachers at SMAIT Al-Fityan, it was identified that while they have utilized digital media such as videos and PowerPoint presentations, they lack experience in creating or using augmented reality (AR)-based learning media. To address this gap, a training program was conducted to enhance teachers’ skills in integrating advanced technology into their teaching practices by creating AR-based flash cards. The training program included several stages: pre-test, training on AR-based flash card creation, hands-on practice with mentoring, and evaluation through post-test and response questionnaires. The results demonstrated a significant improvement in teachers’ abilities, with the average pre-test score of 20 increasing to 80 in the post-test. Furthermore, response questionnaires showed that 72.7% of participants rated the training material as easy to implement (good category). These findings indicate that the training successfully enhanced teachers’ competencies in creating technology-based learning media, which is expected to support innovative and interactive teaching aligned with 21st-century demands.